2019
DOI: 10.1016/j.ceca.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ca2+ signaling by acute hypoxia and acidosis in cardiomyocytes derived from human induced pluripotent stem cells

Abstract: Aims:The effects of acute (100s) hypoxia and/or acidosis on Ca 2+ signaling parameters of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) are explored here for the first time.Methods and Results: 1) hiPSC-CMs express two cell populations: rapidly-inactivating I Ca myocytes (τ i <40ms, in 4-5 day cultures) and slowly-inactivating I Ca (τ i ≥ 40ms, in 6-8 day cultures). 2) Hypoxia suppressed I Ca by 10-20% in rapidly-and 40-55% in slowly-inactivating I Ca cells. 3) Isoproterenol enhanced I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 72 publications
(100 reference statements)
2
9
0
Order By: Relevance
“…Nevertheless, unprimed hPSC-CMs (no maturation protocol applied) still represent a valid reductionist model in dissecting molecular mechanisms within human and cardiac cell backgrounds. For instance, a recent study successfully identified direct inactivation mechanisms of human voltagesensitive L-type calcium channels by molecular O 2 and acidosis (Fernandez-Morales et al, 2019), complementing our findings in murine models (Martewicz et al, 2012). Simultaneously, the authors clearly show how studying more complex functional features requires careful evaluation of cardiac structural maturation, with whole-cell ion dynamics changing following substrate interaction, which our group showed to be mediated by mechanotransduction signaling (Martewicz et al, 2017).…”
Section: Advantages and Limitationssupporting
confidence: 67%
“…Nevertheless, unprimed hPSC-CMs (no maturation protocol applied) still represent a valid reductionist model in dissecting molecular mechanisms within human and cardiac cell backgrounds. For instance, a recent study successfully identified direct inactivation mechanisms of human voltagesensitive L-type calcium channels by molecular O 2 and acidosis (Fernandez-Morales et al, 2019), complementing our findings in murine models (Martewicz et al, 2012). Simultaneously, the authors clearly show how studying more complex functional features requires careful evaluation of cardiac structural maturation, with whole-cell ion dynamics changing following substrate interaction, which our group showed to be mediated by mechanotransduction signaling (Martewicz et al, 2017).…”
Section: Advantages and Limitationssupporting
confidence: 67%
“…Finally, it is worth mentioning that mitochondria may serve as a significant dynamic buffer of [Ca 2+ ] c under physiological conditions on a beat-to-beat basis in other types of cardiomyocytes such as neonatal cardiomyocytes [14], although the MCU complex is not likely to be involved in cytosolic Ca 2+ handling in adult ventricular myocytes. Since neonatal cardiomyocytes, adult atrial myocytes, and cardiomyocytes derived from human induced pluripotent stem cells have fewer T-tubules and smaller gain of Ca 2+ -induced Ca 2+ release compared to adult ventricular myocytes, the MCU complex and/or NCLX may have a larger contribution to cytosolic Ca 2+ handling [14,28,125,126]. Indeed, using genetically engineered mitochondria-targeted Ca 2+ biosensors, several groups clearly showed that spontaneous beating promotes beat-tobeat mitochondrial Ca 2+ uptake in neonatal cardiomyocytes [14,28].…”
Section: Handling In Cardiomyocytesmentioning
confidence: 99%
“…Furthermore, changes in the functionality and electrophysiology have been observed, including decrease in hiPSC-CM beating frequency 11 , 12 , 15 , 16 , 24 , contractility, calcium overload and arrhythmias 14 . In these models, hypoxic conditions have been induced to the hiPSC-CMs by multiple methods, such as by using hypoxic gas 8 10 , 13 15 , 24 , 25 or causing oxidative stress via peroxide treatment 16 . In addition, cell culture media composition has been modified to better recapitulate the ischemic conditions in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cell culture media composition has been modified to better recapitulate the ischemic conditions in several studies. The modifications include removal of glucose 23 or serum 11 , or both 8 10 , 13 , 14 , 22 , as well as acidosis to better mimic the physiological ischemic event 8 10 , 13 , 22 .…”
Section: Introductionmentioning
confidence: 99%